2000
DOI: 10.1094/mpmi.2000.13.10.1092
|View full text |Cite
|
Sign up to set email alerts
|

A Potato Gene Encoding a WRKY-like Transcription Factor Is Induced in Interactions with Erwinia carotovora subsp. atroseptica and Phytophthora infestans and Is Coregulated with Class I Endochitinase Expression

Abstract: A potato gene encoding a putative WRKY protein was isolated from a cDNA library enriched by suppression subtractive hybridization for sequences upregulated 1 h postinoculation with Erwinia carotovora subsp. atroseptica. The cDNA encodes a putative polypeptide of 172 amino acids, containing a single WRKY domain with a zinc finger motif and preceded by a potential nuclear localization site. St-WRKY1 was strongly upregulated in compatible, but only weakly in incompatible, interactions with Phytophthora infestans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 38 publications
0
85
0
2
Order By: Relevance
“…The W-box sequences are known to bind members of the WRKY family of transcription factors . Some members of this family in potato and parsley are induced by pathogen challenge as well (Dellagi et al, 2000;Eulgem et al, 1999). Du and Chen (2000) identified several receptor kinases in Arabidopsis that are possible targets for pathogen-and SA-induced WRKY DNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The W-box sequences are known to bind members of the WRKY family of transcription factors . Some members of this family in potato and parsley are induced by pathogen challenge as well (Dellagi et al, 2000;Eulgem et al, 1999). Du and Chen (2000) identified several receptor kinases in Arabidopsis that are possible targets for pathogen-and SA-induced WRKY DNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…At one hour after infiltration of the 100 nM Avr9 into Cf-9 potato we observed very strong changes in pathogen-responsive genes and are enriched in Arabidopsis promoters of genes involved in systemic acquired resistance . Some WRKY genes analyzed in potato and parsley are induced by pathogen challenge (Dellagi et al, 2000;Eulgem et al, 1999). Asai et al (2002) have shown that in Arabidopsis some WRKY genes play an essential role in genefor-gene pathogen resistance.…”
Section: Hr-related Gene Expression Alteration: Level and Timingmentioning
confidence: 99%
“…WRKY proteins are a major family of plant transcription factors implicated in the regulation of various processes, including pathogen defense (Eulgem et al, 1999;Chen, 2000, 2002;Du and Chen, 2000;Kim et al, 2000;Maleck et al, 2000;Somssich, 2001, 2002;Yu et al, 2001;Cormack et al, 2002;Deslandes et al, 2002;Yoda et al, 2002), wound response (Dellagi et al, 2000;Hara et al, 2000;Yoda et al, 2002), trichome development (Johnson et al, 2002a), and senescence (Hinderhofer and Zentgraf, 2001;Somssich, 2001, 2002;Johnson et al, 2002a). In Arabidopsis thaliana, WRKY proteins consist of 74 members, each defined by the presence of at least one DNA binding WRKY domain, a 60-amino acid stretch that contains the amino acid sequence WRKYGQK and a zinc-finger-like motif .…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the NBS-LRR resistance protein forms the largest class of genes and function as intracellular receptors, which code for proteins with NBS-LRR domains (Bozkurt et al, 2011). The WRKY transcription factor plays key roles as repressors as well as activators in plant developmental processes, as higher expression of transcription related WRKY genes has been reported during the compatible interaction of potato and P. infestans (Dellagi et al, 2000). In potato, most of the chromo domains and gag-pol polyprotein containing proteins have a CCHC zinc finger domains playing broader functions in zinc ion and nucleic acid binding (Lawrencea et al, 2014).…”
Section: Target Prediction Of Mirnas and Functional Analysismentioning
confidence: 99%